Late-onset congenital posterolateral diaphragmatic hernia - Benedetti, Juan Luis; Chavarría, Oscar; Ferrari, Ivone (Cirugía del Uruguay, 1986)
Description of two cases of congenit posterolateral diaphragmatic hernia with tardy clinical manifestation. Embryological consideration of the diaphragm, being the cause of the hernia, the persistence of Bochdalek foramen. Late manifestation may be due to: a) a narrow diaphragmatic orífice; b) temporary obstruction of the orífice by the liver or the spleen; c) the presence of a hernia pocket. Clinically, hernias manifest themselves through respiratory- digestive and/or cardiac symptomatology. They may also be asymptomatic and become a radiological finding, or may first appear as a complication (strangulation), determining a condition of shock and sudden death. Radiology is of primary importance for the diagnosis which will not be invalidated by the existence of prior normal radiological study of the chest. Finaliy, considerations are made on indications of operations and operative times.